2016
DOI: 10.5430/jnep.v6n12p57
|View full text |Cite
|
Sign up to set email alerts
|

Preceptor support to improve nurse competency and satisfaction: A pilot study of novice nurses and preceptors in a pediatric intensive care unit

Abstract: Objective: To develop and implement an evidence-based preceptor program that improves satisfaction and competency among pediatric intensive care nurses. The preparation-practice gap-defined as the discrepancy between new graduates' abilities and the demands of their first jobs-increases stress, turnover, costs and medical errors. Preceptor programs and strong preceptor teaching might be able to narrow this gap. Methods: We developed, implemented and evaluated a Preceptor Support Program to bridge the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Some studies indicate that programmes to improve competency among preceptors increase satisfaction in both novice nurses and preceptors (Hickerson et al, 2016; Kim & Shin, 2017). The work of Wu et al (2014) reports that standard education for nursing practice competency has been shown to enhance clinical competency such as collection of health information, physical assessment, scenario simulation and communication in an experimental group compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that programmes to improve competency among preceptors increase satisfaction in both novice nurses and preceptors (Hickerson et al, 2016; Kim & Shin, 2017). The work of Wu et al (2014) reports that standard education for nursing practice competency has been shown to enhance clinical competency such as collection of health information, physical assessment, scenario simulation and communication in an experimental group compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, a preliminary evaluation of the existing preceptorship model was conducted across the nearly 600-bed organization, which employs 2,644 clinical nursing full-time equivalents and hires nurses at a rate of approximately 500 per year. Hickerson et al (2016) found that a large proportion of nurse preceptors reported a lack of support, low morale, and poor satisfaction with the role. These results indicated that, although the long-standing model may have been adequate in meeting nursing onboarding demands, the institution had significant room for improvement.…”
Section: Needs Assessmentmentioning
confidence: 99%
“…However, these checklists were designed to ensure that NGNs had received training and mastered certain skills, rather than focused on completion of specific daily tasks. Most of the research regarding NGN orientation program improvement initiatives involves preceptor development and training (Hickerson et al, 2016; Senyk & Staffileno, 2017). One review evaluated various strategies utilized in the literature to develop critical thinking skills in NGNs and concluded that preceptors were critical to developing the critical thinking skills of NGNs, regardless of strategy used (Schuelke & Barnason, 2017).…”
Section: Available Knowledgementioning
confidence: 99%